Ambiguitas dan Distorsi Makna dalam Al-Qur’an - Salamah, Ummu; Latifah, Ira Ainul; Nisa, Mauidlotun; Susiawati, Wati (Mauriduna: Journal of Islamic Studies, 2025)
Penilitian ini membahas tentang ambiguitas dan distorsi makna yang terdapat dalam surat di dalam Al-Qur'an. Dalam kajian semantik, ambiguitas atau ketidak jelasan makna dapat disebabkan oleh beberapa hal, di antaranya adalah kata yang memiliki sifat umum atau kalimat yang tidak pernah seratus persen homogen. Sedangkan distorsi terjadi akibat kurangnya pengetahuan atau tindakan dari setiap individu yang ingin memahami ayat tersebut sesuai keinginannya dan ingin merangsang orang lain agar menyimpang dari pemahaman makna ayat Al-Qur'an. Dengan menggunakan metode metode kajian pustaka (literature review), peneliti mencoba mengumpulkan bahan materi secara sistematis tentang ambiguitas dan distorsi makna yang terdapat dalam beberapa ayat al-Qur’an dari penelitian-penelitian yang terdahulu. Dalam penelitian ini, penulis memaparkan contoh-contoh ambiguitas dan distorsi makna dalam al-Qur’an. Terdapat ambiguitas makna pada surah al-Baqarah ayat 228 dan an-Nisa ayat 43 dari penelitian Kamaluddin Abunawas, surah al-Baqarah ayat 223 dan an-Nisa ayat 34 pada penelitian Iswah Adriana, surah al-Baqarah ayat 220 pada penelitian Salman dkk.. Dan terdapat distorsi makna pada surah al-Baqarah ayat 191 dan 255 dari penelitian Septiani dkk., surah Thaha ayat 121, an-Nisa ayat 164, al-A’raf ayat 179 dari penelitian Nirwana AN. Serta dalam penelitian ini penulis juga berusaha memberikan sikap menghadapi ambiguitas dan distorsi makna dalam ayat al-Qur’an. This research discusses the ambiguity and distortion of meaning contained in letters in the Al-Qur'an. In semantic studies, ambiguity or unclear meaning can be caused by several things, including words that have general characteristics or sentences that are never one hundred percent homogeneous. Meanwhile, distortion occurs due to a lack of knowledge or action on the part of each individual who wants to understand the verse according to his wishes and wants to stimulate other people to deviate from understanding the meaning of the verse of the Qur'an. By using the literature review method, the researchers tried to collect material systematically about the ambiguity and distortion of meaning contained in several verses of the Qur'an from previous studies. In this research, the researchers describe examples of ambiguity and distortion of meaning in the Qur'an. There is ambiguity in the meaning of surah al-Baqarah verse 228 and an-Nisa verse 43 from Kamaluddin Abunawas' research, surah al-Baqarah verse 223 and an-Nisa verse 34 in Iswah Adriana's research, surah al-Baqarah verse 220 in Salman et al.'s research. And there is a distortion of meaning in surah al-Baqarah verses 191 and 255 from Septiani et al.'s research, surah Thaha verse 121, an-Nisa verse 164, al-A'raf verse 179 from AN's Nirvana research. And in this research the researchers also try to provide an attitude towards facing ambiguity and distortion of meaning in the verses of the Qur'an.